DNA profiling of F1 Hybrid in Bambara Groundnut (Vigna subterranea L. Verdc.) using Simple Sequence Repeat Marker - Ahmad, Nariman S. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Bambara groundnut (Vigna subterranea L. Verdc.) is an indigenous crop of African origin. It is considered as a drought tolerant and the third most important leguminous crop in Sub-Saharan Africa due to its agronomic and nutritional potential. Screening of presumed hybrids and progenies with molecular marker proved to be more accurate and reliable compared to morphological characterizations. Testing the accuracy of presumed hybrids resulted from the cross of African and Indonesia landraces were performed using 12 SSR markers. Out of five crosses only one hybrid resulted from the cross BC x S19 was confirmed to be genuine with four polymorphic markers. The seeds of other crosses were found to come from the self-pollination of maternal parent. These results clearly demonstrate that SSR markers should be useful for rapid identification of true hybrid at the early stage of growth. Hence, the technique contributes to genotype the progenies more accurately to develop genetic mapping and QTL analysis, aiming towards more efficient utilization, conservation and development of bambara groundnut germplasm.
Keywords: Bambara groundnut; SSR marker; capillary electrophoresis; F1 hybrid